Investigation of the physicochemical properties of Bi,Ca-doped BaZrO3 perovskites - Akyuz, Serra Melek; Figen, Halit Eren; Elibol, Meltem Karaismailoglu (ROYAL SOC CHEMISTRY, 2023)
Perovskite oxides, primarily the ones based on BaZrO3, hold significant interest for diverse applications in a variety of disciplines, such as electrocatalysts or electrolytes in fuel cell technologies. This study outlines the synthesis of BaZrO3 perovskite powders via a sol-gel route, and explores the incorporation of bismuth and calcium cations through single doping. Extensive characterization, encompassing X-ray diffraction, thermogravimetric analysis, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis, oxygen/hydrogen temperature-programmed desorption/reduction, and scanning electron microscopy/energy-dispersive X-ray spectroscopy, reveals the impact of the metal cation incorporation on physicochemical properties, enhancing oxygen vacancies and lattice oxygen species within the BaZrO3 perovskite structure.
Keywords: OXYGEN REDUCTION; OXIDE; BABIO3; CONDUCTIVITY; NANOPOWDERS; SOFC; Chemistry